Preserving Past Tastes - Ureczky, Eszter (Hungarian Journal of English and American Studies, 2021)
Book review: Wall, Wendy. Recipes for Thought: Knowledge and Taste in the Early Modern English Kitchen. Philadelphia: U of Pennsylvania P, 2016. 328 pages. ISBN 9780812247589. 69.95.